1992
DOI: 10.1111/j.1476-5381.1992.tb14451.x
|View full text |Cite
|
Sign up to set email alerts
|

Human bronchial cyclic nucleotide phosphodiesterase isoenzymes: biochemical and pharmacological analysis using selective inhibitors

Abstract: 1 The aims of the present study were to characterize the cyclic nucleotide phosphodiesterase (PDE) isoenzyme activities present in human bronchi and to examine the ability of selective isoenzyme inhibitors to relax histamine and methacholine precontracted preparations of human bronchi. 2 Three separations of pooled human bronchial tissue samples were performed. Ion-exchange chromatography showed that the soluble fraction of human bronchial preparations contains PDE I, II, III, IV and V isoenzyme activities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
88
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(93 citation statements)
references
References 28 publications
4
88
0
Order By: Relevance
“…Inhibition of PDE3/4 has previously been reported to induce relaxation of canine airways, guinea pig trachea, and human ASM preparations (de Boer et al, 1992;Naline et al, 1996;Torphy, 1998;Boswell-Smith et al, 2006b). We have demonstrated that the selective inhibition of PDE3/4 by RPL554 elicited relaxation of bronchial tone in human isolated airways, which extends and supports observations previously reported in guinea pig isolated trachea with this drug Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of PDE3/4 has previously been reported to induce relaxation of canine airways, guinea pig trachea, and human ASM preparations (de Boer et al, 1992;Naline et al, 1996;Torphy, 1998;Boswell-Smith et al, 2006b). We have demonstrated that the selective inhibition of PDE3/4 by RPL554 elicited relaxation of bronchial tone in human isolated airways, which extends and supports observations previously reported in guinea pig isolated trachea with this drug Fig.…”
Section: Discussionmentioning
confidence: 99%
“…under conditions similar to those described by Tomkinson et al (1993) on the airways of guinea-pig, cow, pig and mousetend to support previous observations and suggest that there may be a similar relationship between P2-adrenoceptors and PDE type IV in the human bronchus since rolipram seems to be as potent (or slightly more potent) than isoprenaline and salbutamol, and about 10 fold more potent than siguazodan. Since both rolipram and the selective PDE III inhibitor Org 9935 were potently active at concentrations required for selectivity (de Boer et al, 1992), both PDE III and IV may be important in regulating contractility. Indeed de Boer et al (1992) demonstrated that equally potent inhibition of methacholine-induced contractions was seen with selective type IV and type III cyclic AMP PDE inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Since both rolipram and the selective PDE III inhibitor Org 9935 were potently active at concentrations required for selectivity (de Boer et al, 1992), both PDE III and IV may be important in regulating contractility. Indeed de Boer et al (1992) demonstrated that equally potent inhibition of methacholine-induced contractions was seen with selective type IV and type III cyclic AMP PDE inhibitors. This was not the case in our study where rolipram was 10 fold more potent than siguazodan.…”
Section: Discussionmentioning
confidence: 99%
“…Airway smooth muscle relaxation is observed following inhibition of PDE3 or PDE4 in canine (Torphy et al, 1988;Torphy and Undem, 1991), guinea pig trachea (Raeburn et al, 1993;Spina et al, 1995), and human airway preparations (de Boer et al, 1992;Rabe et al, 1995), which is primarily thought to be mediated by PDE3 (Cortijo et al, 1993). RPL554 and RPL565 both caused a concentration-and timedependent inhibition of contractile responses elicited by EFS.…”
Section: Discussionmentioning
confidence: 99%